(untitled) (Research, Society and Development, 2022)
Exclusive Breastfeeding (EBF) is the best and most efficient source of nutrition for the infant, providing gains for the baby and the mother. With this, the objective was to investigate the benefits of exclusive breastfeeding in the first six months of the newborn’s life, both for the mother and for the baby’s development, as well as factors related to breastfeeding difficulties for lactating women. This study is a narrative review of the literature, carried out in the Medline and SCIELO databases, with the descriptors and search strategy “Maternal Breastfeeding” AND “Child Development”, in Portuguese, English and Spanish, to search for these terms in the title, abstract or body of studies. The inclusion criteria corresponded to productions available in full, which allow for better consistency with the theme developed in this research, published between 2015 and 2021. The research identified the importance of breastfeeding in early life, as breast milk is a complete food for nutrition of the infant and its benefits transcend nutritional barriers and reach immunological factors. In the same way, the benefits for the lactating woman who maintain breastfeeding are evident, however, the various difficulties reported by them related to the establishment of breastfeeding are notable. This study reinforced that breastfeeding in its entirety offers numerous benefits, such as reducing the percentage of morbidity, comorbidities and infant mortality, in addition to benefiting the mother in uterine involution and weight loss, in addition to providing protection against ovarian and breast cancer. Thus, EBF should preferably be maintained until the first six months postpartum.